ABM : organization and management : concepts, caselets and exercises - Garalde-Orjalo, Victoria; Frias, Solita A. (Quezon City : Phoenix Publishing House, Inc., 2016)
"This book covers the organization and management concepts serve as guidelines for professions or academic programs in science, technology, and engineering, as they cover general course sketches of these trades. It focuses on organization and management concepts through developments in the Philippine economy, as well as global statistics. The caselets and exercises drill the students in the use of the ABM, with particular emphasis on organization and management theories in diverse environments".
Includes references.
English text.
Keywords: Management